The global health crisis : ethical responsibilities / Thana Cristina de Campos. - Campos, Thana Cristina de (Cambridge bioethics and law., 2017)
Proposing a new view of global justice based on natural law, this book presents a discussion of the key ethical values in contemporary medicine and health, notably in relation to neglected diseases like malaria, Ebola and Zika. The lack of treatments for such diseases point to a global health crisis. Thana Cristina de Campos provides a general framework, based on global commutative justice, for discussion of the ethical responsibilities of international stakeholders, mapping the varying duties they have, and their content and force. She also addresses the urgent need for reforms to the international legal rules on bioethics, notably the system of intellectual property rights. These ideas will be of interest to those who are looking for a more nuanced view of the human right to health than that provided by advocates in the globalist mainstream.